THE CHEMICAL COMPOSITION OF DRIED RED SEAWEED (Eucheuma cottonii) - Indra Agusman; Andarini Diharmi; Nur Ira Sari (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
ABSTRACT Eucheuma cottonii is a species of brown seaweed with high nutritional value. This study aims to determine the chemical composition of red seaweed E. cottonii. The research method used is experimental by conducting a series of experiments. The treatment used was to make E. cottonii seaweed flour before being analyzed. This study consisted of two stages, namely: 1) Sample preparation, 2) Analysis of the chemical composition of E. cottonii flour consisting of water, ash, protein, fat and carbohydrate content (by difference). The results showed that the chemical composition of dry E. cottonii consisted of moisture content 26.51% (db), ash 17.27% (db), protein 10.73% (db), fat 2.59% (db) and carbohydrates 42.9% (db). The carbohydrate content is the highest and the lowest in fat.Keywords: carbohydrate, chemical composition, seaweed